Development of flavour tagging algorithms for Run 3 at LHCb - Olocco, Micol (Technische Universität Dortmund, 2025)
This thesis investigates the role of automation and machine-learning techniques as a methodological bridge between high-energy physics and industry, within the framework of the SMARTHEP European Training Network. The core scientific contribution of this thesis is the development of flavour-tagging algorithms for the LHCb Upgrade I. The performance of the developed algorithms is evaluated using data collected by the LHCb experiment in 2024 and demonstrates stable behaviour in the upgraded detector environment. These algorithms constitute the first flavour-tagging implementation specifically developed for Run 3, enabling time-dependent measurements of neutral B-meson mixing and CP violation. Automation principles are further applied to the development of an infrastructure for the deployment and validation of Trigger Configuration Keys at LHCb, designed to support Run 3 data-taking and operations. Beyond the core LHCb physics programme, this thesis presents the design of an open-source framework for the automated generation of synthetic financial transaction data using large language models. Such synthetic datasets provide a practical alternative for fraud-detection research, where access to real financial data is constrained by privacy and regulatory requirements.

Diese Dissertation untersucht die Rolle von Automatisierung und Machine-Learning-Methoden als Brücke zwischen der Hochenergiephysik und der Industrie im Rahmen des SMARTHEP European Training Network. Der zentrale wissenschaftliche Beitrag dieser Arbeit ist die Entwicklung von Flavour-Tagging-Algorithmen im Zuge des Upgrade I des LHCb-Experiments. Die Performanz der entwickelten Algorithmen wird anhand von im Jahr 2024 vom LHCb-Experiment aufgezeichneten Daten evaluiert und zeigt ein stabiles Verhalten für den aufgerüsteten Detektor. Diese Algorithmen stellen die ersten speziell für Run 3 entwickelten Flavour-Tagger dar und ermöglichen zeitabhängige Messungen der Mischung neutraler B-Mesonen sowie der CP-Verletzung. Automatisierungsprinzipien werden zudem bei der Entwicklung der Infrastruktur zur Bereitstellung und Validierung von Trigger Configuration Keys am LHCb-Experiment angewendet. Die Automatisierung ist zur Unterstützung der Datennahme und des Betriebs des Detektors während Run 3 konzipiert. Über das zentrale Physikprogramm des LHCb-Experiments hinaus präsentiert diese Dissertation die Konzeption eines Open-Source-Frameworks zur automatisierten Erzeugung synthetischer Finanztransaktionsdaten mithilfe von Large Language Models. Solche synthetischen Datensätze stellen eine praktikable Alternative für die Forschung zur Betrugserkennung dar, da der Zugang zu echten Finanzdaten durch Datenschutz- und regulatorische Anforderungen stark eingeschränkt ist.
From high-energy physics to financial transactions: automation as a unifying principle
Keywords: High energy physics; Flavour physics; LHCb; Machine learning; 530; Hochenergiephysik; LHCb (Teilchendetektor); Maschinelles Lernen